Trends and Factors Associated With Concordance Between International Classification of Diseases, Ninth and Tenth Revision, Clinical Modification Codes and Stroke Clinical Diagnoses. Issue 8 (August 2019) - Chang, Tiffany E.; Tong, Xin; George, Mary G.; Coleman King, Sallyann M.; Yin, Xiaoping; O'Brien, Suzanne; Ibrahim, Ghada; Liskay, Alice; Wiltz, Jennifer L.
Abstract : Background and Purpose—: International Classification of Diseases, Ninth and Tenth Revision, Clinical Modification ( ICD-9-CM and ICD-10-CM ) codes are often used for disease surveillance. We examined changes in concordance between ICD-CM codes and clinical diagnoses before and after the transition to ICD-10-CM in the United States (October 1, 2015), and determined if there were systematic variations in concordance by patient and hospital characteristics. Methods—: We included Paul Coverdell National Acute Stroke Program patient discharges from 2014 to 2017. Concordance between ICD-CM codes and the clinical diagnosis documented by the physician (assumed as accurate) was calculated for each diagnosis category: ischemic stroke, transient ischemic attack, subarachnoid hemorrhage, and intracerebral hemorrhage. Results—: In total, 314 857 patient records were included in the analysis (n=280 hospitals), 55.9% of which were obtained after the transition to ICD-10-CM . While concordance was generally high, a small, and temporary decline occurred from the last calendar quarter of ICD-9-CM (average unadjusted concordance =92.8%) to the first quarter of ICD-10-CM use (91.0%). Concordance differed by diagnosis category and was generally highest for ischemic stroke. In the analysis of ICD-10-CM records, disagreements often occurred between ischemic stroke and transient ischemic attack records and between subarachnoid and intracerebral hemorrhage records. Compared with the smallest hospitals (⩽200 beds), larger hospitals had significantly higher odds of concordance (ischemic stroke adjusted odds ratio for ≥400 beds, 1.7; 95% CI, 1.5–1.9). Conclusions—: This study identified a small and transient decline in concordance between ICD-CM codes and stroke clinical diagnoses during the coding transition, indicating no substantial impact on the overall identification of stroke patients. Researchers and policymakers should remain aware of potential changes in ICD-CM code accuracy over time, which may affect disease surveillance. Systematic variations in the accuracy of codes by hospital and patient characteristics have implications for quality-of-care studies and hospital comparative assessments. Abstract : Supplemental Digital Content is available in the text.